Oxaliplatin-Loaded Chitosan Nanoparticles Decorated with Cetuximab Single-Chain Variable Fragment for Human Colorectal Cancer Treatment - Khadijeh Falahzadeh; Fariba Esmaeili; Leila Nematollahi; Elham Bayat; Mehdi Khoobi; Mohammadali Mazloomi; Masumeh Jalalvand; Reza Faridi Majidi; Babak Negahdari (Cell Journal)
Objective: Colorectal cancer (CRC) is the second leading cause of cancer-related deaths worldwide. Engineeredbiomolecules can be used as a targeted tool to deliver drugs directly to tumors that reduce the adverse effects of conventionaltreatments. We aimed to prepare non-targeted oxaliplatin-loaded chitosan nanoparticles (OXPT-CS NPs) and targetedOXPT-CS NPs decorated with cetuximab single-chain variable fragment (scFv) to send both NPs to epidermal growth factorreceptor (EGFR) overexpressing HCT 116 cells, a human colorectal carcinoma cell line, for comparing their cytotoxicity.Materials and Methods: In this experimental study, OXPT-CS NPs were synthesized using a fluid system. Encapsulationefficiency percentage (EE%) and oxaliplatin release rate were evaluated. Western blot and cell-based ELISA confirmed scFvproduction and its binding ability to EGFR, respectively. The Fourier transform infrared spectroscopy (FTIR) determinedthe conjugation of scFv to OXPT-CS NPs. The NPs were characterized, and their toxicity against the HCT 116 cells wasevaluated using 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) and flow cytometry assays.Results: The EE% of OXPT-CS NPs was 93%, and the average diameters were 75.85 ± 8.81 nm and 92.48 ± 9.51before and after scFv conjugation, respectively. The scFv was purified via affinity chromatography. The western blotmethod and cell-based ELISA revealed successful purification of scFv and its attachment to EGFR on HCT 116 cells.The FTIR analysis determined the interactions between the scFv and OXPT-CS NPs. According to MTT and flowcytometry results, the targeted delivery system significantly reduced HCT 116 cancer cell viability and increasedapoptosis induction up to 99.8%.Conclusion: The scFv-OXPT-CS NPs demonstrated an increased cytotoxic function due to the presence of scFv in itsformulation. This delivery system offers a promising method for delivering chemotherapy drugs to cancer cells. Moreresearch is needed on the best strategies for improving treatment efficacy by targeting cancer cells.